The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1447-0756.2010.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign cystic mesothelioma: A case series with one case complicated by pregnancy

Abstract: Benign cystic mesothelioma (BCM) is a rare tumor of unknown origin, most frequently encountered in women of reproductive age and with unknown etiology. Most patients have a history of previous pelvic operation, endometriosis, or pelvic inflammatory disease. Preoperative diagnosis is difficult. We report the cases of three patients, with one case complicated by pregnancy, and discuss the diagnostic evaluation and treatment of this rare disease. Complete surgical resection is recommended if feasible. However, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Owing to this pattern it has been suggested that the cysts are at least in part hormonally driven, likely by oestrogen. Given this, it is surprising that there are very few reports of mesothelial cyst occurrence during pregnancy 6. One report described the incidental finding of a mesothelial cyst in the right iliac fossa during a caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this pattern it has been suggested that the cysts are at least in part hormonally driven, likely by oestrogen. Given this, it is surprising that there are very few reports of mesothelial cyst occurrence during pregnancy 6. One report described the incidental finding of a mesothelial cyst in the right iliac fossa during a caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…They pertain to the peritoneum, can have mass effect, are filled with fluid and can include haemorrhagic components. The classic appearance on ultrasound is a spider web or honeycomb pattern 11 17. However, PICs can present as very complex lesions on the ovarian surface, hence mimicking an ovarian malignancy 12.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases have also been described in vaginal tunic [5]. Most papers about the disease are case reports [1,5,8] and clinical series, the largest with 17 patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, abnormalities in the development could lead to formation of cysts in the mesothelial [5,10]. This injury has no association with exposure to amianto [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation